2017
DOI: 10.1248/yakushi.16-00263
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing Using the Guidelines for Medical Treatment and Its Safety in the Elderly and Changes in Patient QOL and Activities of Daily Living

Abstract: Pharmacists applied deprescribing, which is a process for the rational use of drugs, for 13 at-home patients. The standard used for the rational use of drugs was the``Guidelines for Medical Treatment and Its Safety in the Elderly'' (the Guidelines). The results of the deprescribing were discussed with physicians to determine prescriptions. After the prescription change, activities of daily living (ADL) and QOL were assessed using the Barthel Index and SF-36v2, respectively. Potentially inappropriate medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
8
0
3
Order By: Relevance
“…Actually, the usage rate of potentially inappropriate drugs according to the BCJV (24.0%) in our study was lower than that in previous reports (43.6-56.1%). [19][20][21] According to a survey conducted in the United States, adverse reactions occurred in 10% or more of elderly outpatients and in 15-20% of residents in elder-care facilities every year. 30) The present survey focused exclusively on adverse reactions in patients who received drugs listed in the BCJV and GL2015, and we found that the incidence rates ranged from 3.0-8.2% in inpatients and outpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the usage rate of potentially inappropriate drugs according to the BCJV (24.0%) in our study was lower than that in previous reports (43.6-56.1%). [19][20][21] According to a survey conducted in the United States, adverse reactions occurred in 10% or more of elderly outpatients and in 15-20% of residents in elder-care facilities every year. 30) The present survey focused exclusively on adverse reactions in patients who received drugs listed in the BCJV and GL2015, and we found that the incidence rates ranged from 3.0-8.2% in inpatients and outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Three investigations conducted in Japan reported that 43.6-56.1% of drug prescriptions are potentially inappropriate for elderly inpatients based on the BCJV. [19][20][21] The GL2015 has been reported to be a useful support tool for making decisions regarding dose reduction and discontinuation processes in home-care patients. 22) There has been no report on adverse drug reactions of potentially inappropriate prescriptions and related medical costs that could be avoided using the BCJV and GL2015 in both inpatient and outpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…This led 5As we explore the roles of the modern geriatricians it involves care for older persons in multiple sites: Hospital, community, rehabilitation facilities, nursing homes and home care. While much of its original focus was on rehabilitation of disabilities as in the Geriatric Evaluation and Management Unit (6), it also spread to enhanced hospital care focused on recognizing the geriatric giants of Bernard Isaacs (7) and caring for those with delirium (8-10) and recognizing the need for deprescribing (11). In the USA, the American Medical Directors Association has made major advances in the care of older persons in nursing homes (12).…”
Section: Figurementioning
confidence: 99%
“…A retrospective cohort study of 569 older adults admitted to a rehabilitation ward reported an association between a decrease in the Beers criteria PIMs and improvement in the Functional Independence Measure‐Motor at discharge 31 . In Japan, the application of the Japan Geriatrics Society's Guidelines for Medical Treatment and its Safety in the Elderly 2015 16 was reported to be a useful tool for deprescribing 32 . However, the effect of explicit criteria intervention on clinically significant endpoints, such as death and rehospitalization, is unclear.…”
Section: Resultsmentioning
confidence: 99%